AHP-SPIRE: Edukasi Pemilu Sehat dan Bertanggung Jawab Untuk Pemilih Pemula - Fahmi, Amiq; Mulyanto, Edy; Sugiarto, Edi; Pramudi, Yuventius Tyas Catur; Budiman, Fikri (Jurnal Pengabdian Literasi Digital Indonesia, 2024)
In Indonesia, general elections are a fundamental democratic process to elect leaders, both the President and Regional Heads, such as Governors, Mayors, and Regents. The selection of suitable and qualified leaders determines the success of a nation, state, and region in welcoming Golden Indonesia 2045. This community service program aims to provide healthy and responsible election education to permanent voters registered and verified by the KPU, especially novice voters with the right to vote. This community service proposes the application of the Analytic Hierarchy Process (AHP) with SPIRE (Spiritual, Physical, Intellectual, Relationship, and Emotional) criteria as an effective tool for selecting suitable and ideal leadership candidates, both President and Regional Head, among novice voters in grades XI and XII SMA. AHP-SPIRE is a multi-criteria method that allows structured and measurable decision-making based on consideration of various important factors for presidential, Governor, Regent, or Mayor candidates. Ultimately, novice voters, especially students in grades XI and XII, have better decision-making techniques based on the expected criteria.